Evaluation of the safety and quality of Brazil nuts (Bertholletia excelsa) using the tools of dna sequencing technology and aflatoxin profile - Esperança, Victor J. R.; Moreira, Paula I. O.; Chávez, Davy W. H.; Freitas-Silva, Otniel (Frontiers in Nutrition, 2024)
Brazil nuts (BN) result from sustainable extraction and are widely exploited in the Amazon region.Due to the production characteristics in the forest and the nutritional characteristics of these nuts, the occurrence of fungal contamination and the presence of aflatoxins are extensively discussed in the literature as a great aspect of interest and concern. This study aims to evaluate the microbial profile through DNA sequencing and amplification of 16S and ITS genes for bacterial and fungal analysis, respectively) and the presence of mycotoxins by HPLC-FD from different fractions of the nuts processing. The BN samples, harvest A (HA) and harvest B (HB), from two different harvests were collected in an extractive cooperative in the Amazon region for microbiological analysis (from DNA extraction and amplification of 16S genes bacteria analysis and ITS for fungi) and mycotoxins (aflatoxins AFB1, AFB2, AFG1 and AFG2) by HPLC-FD / KobraCell®. The samples showed a very different microbiome and aflatoxin profile. Genres such as Rothia (HA) and Cronobacter (HB) were abundant during the analysis of bacteria; as for fungi, the genera Aspergillus, Fusarium, Penicillium, and Alternaria were also considered prevalent in these samples. Soil microorganisms, pathogenic and related to inadequate hygienic-sanitary production practices and aflatoxins, were found in the samples but within the established limits permitted by Brazilian legislation. Nuts have a diverse microbiota and are not restricted to fungi of the genus Aspergillus. The microbiological and toxicological profile can be quite variable within the same nut in the same extraction region and be maximized by global climate changes. Therefore, it is necessary to advance sanitary educational actions in applying good production practices and inspection programs to ensure the sustainability and quality of the BN production chain.